Renewable Sources of Energy in Poland - photovoltaics - Babula, Mateusz (Journal of Education, Health and Sport, 2017)
Summary: Photovoltaics is used for producing the electric energy from the solar radiation. These installations are becoming more and more popular. Their main advantage is the possibility of being mounted at any place without the significant interference into the landscape. They can be used by household and/or the produced energy can be sold. Due to the obligation concerning the provision of 15.5% of energy coming from the renewable sources of energy by Poland in 2020, the solar energy can have a significant impact on the shape and work of national distribution network.